ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIS PADA MATERI BANGUN DATAR DI SEKOLAH DASAR - Tegar Ananda, - (2021)
This study aims to obtain a comprehensive picture of the difficulties experienced by students in solving mathematical problems in flat shape material in elementary schools. The research design used was qualitative with a case study method. The subjects of this study involved students, parents, and teachers in one of elementary school in Purwakarta. The researcher conducted a mathematical problem solving test on the students and continued by giving a questionnaire. Researchers also conducted interviews with students, parents and teachers. The research findings showed that some students had difficulty solving mathematical problems. This can be seen from the test results which show a score below 70. The results of questionnaires and interviews show that difficulties occur because students have not mastered arithmetic operations, have not understood the concept of flat shapes, have not maximized learning motivation, have not understood reading comprehension, as well as external factors less supportive.